Fouling characteristics and autopsy of a PES ultrafiltration membrane in cyclodextrins separation - A. M., Mimi Sakinah (Elsevier B.V., 2007)

(untitled)
This paper studies the fouling characteristics and effect of chemical cleaning (alkaline and acidic solution) on PES ultrafiltration membrane during separation of cyclodextrins from starch and CGTase. The fouled membrane surface was observed under scanning electron microscopy (SEM). The ATR/FTIR spectrometry was applied to examine the adsorption of organic elements. The quantitative analysis of the extracted chemical solution was measured by using UV-spectrophotometer and total organic carbon (TOC). The Resistance-In-Series Model was used to identify the responsible hydraulic resistances. The overall results indicated that the adsorption of solutes (CDs or starch byproducts)onto the membrane surface and pores exhibited the highest percentage compared to other fouling mechanisms due to the steric conditions. The measured flux recovery of enzymatic membrane reactor for CDs production was about 95% after chemical cleaning with the alkaline solution